Somatic health among heroin addicts before and during opioid maintenance treatment: a retrospective cohort study - Brekke Mette; Skeie Ivar; Lindbæk Morten; Waal Helge (BMC, 2008)
Abstract Background The long-term impact of opioid maintenance treatment (OMT) on morbidity and health care utilization among heroin addicts has been insufficiently studied. The objective of this study was to investigate whether health care utilization due to somatic disease decreased during OMT, and if so, whether the reduction included all kinds of diseases and whether a reduction was related to abstinence from drug use. Methods Cohort study with retrospective registration of somatic disease incidents (health problems, acute or sub-acute, or acute problems related to chronic disease, resulting in a health care contact). Medical record data were collected from hospitals, Outpatients' Departments, emergency wards and from general practitioners (GPs) and prospective data on substance use during OMT were available from 2001 onwards. The observation period was five years before and up to five years during OMT. The cohort consisted of 35 out of 40 patients who received OMT between April 1999 and January 2005 in a Norwegian district town. Statistical significance concerning changes in number of incidents and inpatient and outpatient days during OMT compared with the pre OMT period was calculated according to Wilcoxon signed rank test. Significance concerning pre/during OMT changes in disease incidents by relation to the type of health service contacts, as well as the impact of ongoing substance use during OMT on the volume of contacts, was calculated according to Pearson chi-square and Fisher's exact tests. Results 278 disease incidents were registered. There was a reduction in all incidents by 35% (p = 0.004), in substance-related incidents by 62% (p < 0.001) and in injection-related incidents by 70% (p < 0.001). There was an insignificant reduction in non-fatal overdose incidents by 44% (p = 0.127) and an insignificant increase in non-substance-related incidents by 13% (p = 0.741). Inpatient and outpatient days were reduced by 76% (p = 0.003) and 46% (p = 0.060), respectively. The disease incidents were less often drug-related during OMT (p < 0.001). Patients experienced a reduction in substance-related disease incidents regardless of ongoing substance use, however there was a trend towards greater reductions in those without ongoing abuse. Conclusion Although as few as 35 patients were included, this study demonstrates a significant reduction in health care utilization due to somatic disease incidents during OMT. The reduction was most pronounced for incidents related to substance use and injection. Inpatient and outpatient days were reduced. Most probably these findings reflect somatic health improvement among heroin addicts during OMT.